Species of Lensia (Cnidaria: Hydrozoa: Siphonophorae) from southeastern Brazilian waters - Eric Y. Nishiyama; Enilma M. Araujo; Otto M.P. Oliveira (Zoologia (Curitiba))
ABSTRACT The siphonophores of the Brazilian coast are poorly studied, despite their abundance and ecological importance. Lensia is the most diverse genus within Siphonophora, with twenty-six valid species. A total of twenty species of Lensia are recorded for South American marine waters. This study presents morphological descriptions and an identification key to the species of Lensia that were collected in two oceanographic campaigns throughout the southeastern Brazilian coast. A total of sixty-one specimens were photographed, described, schematized and measured, and fifteen species of Lensia were identified.